Ministry of Tourism Decree No. 623 Of The Year 2015 Issued on 18/5/2015 = وزارة السياحة قرار رقم 623 لسنة 2015 صادر بتاريخ 18/5/2015 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic